2022
DOI: 10.1186/s12951-022-01590-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Ti3C2Tx MXene promotes electrophysiological maturation of neural circuits

Abstract: Background The ideal neural interface or scaffold for stem cell therapy shall have good biocompatibility promoting survival, maturation and integration of neural stem cells (NSCs) in targeted brain regions. The unique electrical, hydrophilic and surface-modifiable properties of Ti3C2Tx MXene make it an attractive substrate, but little is known about how it interacts with NSCs during development and maturation. Results In this study, we cultured NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…The stimulation of several targets could be accomplished by the fast tuning of galvo mirrors or the shaping of the wavefront phase of the laser by using spatial light modulators. In this regard, laser excitation promotes the precision and specificity of activation of cochlear cells, which provides profound insights into the molecular mechanism of cochlear development and thus benefits populations suffering from sensorineural hearing loss. …”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of several targets could be accomplished by the fast tuning of galvo mirrors or the shaping of the wavefront phase of the laser by using spatial light modulators. In this regard, laser excitation promotes the precision and specificity of activation of cochlear cells, which provides profound insights into the molecular mechanism of cochlear development and thus benefits populations suffering from sensorineural hearing loss. …”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that MXene can form an efficient neural interface for neuron activity, expanding the potential for biosensors, prosthesis, and other neurologic applications. [ 160 ]…”
Section: Materials Modification Strategies For Enhanced Neural Electr...mentioning
confidence: 99%
“…These results indicated that MXene can form an efficient neural interface for neuron activity, expanding the potential for biosensors, prosthesis, and other neurologic applications. [160] Considering that the fabrication of high-resolution neural interfaces based on precious metals and nanostructured materials is usually expensive and time-consuming, and flexibility is also undesirable. While the solution treatment is a low-cost and costeffective manufacturing approach, however, there is still a lack of biocompatible conductive inks that match the properties of traditional metals.…”
Section: Emerging 2d Materials (Especially Mxenes)mentioning
confidence: 99%
“…Biomaterials Science tion neural interfaces for neuroelectronic devices, developing neuro-receptor-mediated synapse devices, and promoting the electrophysiological maturation of neural circuits. 94,95 Remarkably, these 2D materials have been studied in the design of electrochemical sensors for the detection of neurotransmitters (e.g., dopamine, serotonin, epinephrine, norepinephrine, and γ-aminobutyric acid). 96,97 However, there are several challenges associated with MXenes that need to be addressed to fully realize their potential, including oxidative stability, interlayer distance, biosafety issues, over-etching, limited scalability, and limited understanding of the properties.…”
Section: Reviewmentioning
confidence: 99%